Drawing Close to the Brokenhearted: Pastoral Responses to Parents Grieving Stillbirth - Petro, Susannah J. (Journal of pastoral care & counseling, 2015)
Despite its prevalence worldwide, stillbirth is poorly understood and rarely discussed. Accordingly, ministers and other pastoral caregivers are seldom prepared to counsel and console parents suffering from this type of infant loss and to effectively design, propose, and lead ministries within their faith communities for this grieving population. This article addresses the immediate pastoral needs of bereaved parents and proposes first and second order responses that ministers and faith communities can employ to compassionately and effectively care for parents suffering from the trauma of stillbirth.